Great Satan's rage : American negativity and rap/metal in the age of supercapitalism - Wilson, Scott (Book collections on Project MUSE., 2015)
This book looks at how rap and metal have been highly engaged with America's role in the world, supercapitalism and their own role within it. This has especially been the case when genres - hitherto clearly identified as indelibly 'black' or 'white' forms of music - have crossed over as an effect of cross-racial forms of identification and desire, marketing strategy, political engagement, opportunism and experimentation. It is how examples of these forms have negotiated, contested, raged against, survived, exploited, simulated and performed 'Satan's rage' that is the subject of this book. The.